Monitoring training load, muscle damage, and body composition changes of elite indian rowers during a periodized training program - Das, A.; Kaniganti, U. S.; Shenoy, S. J.; Majumdar, P.; Syamal, A. K. (Journal of Science in Sport and Exercise, 2023)
Purpose The purpose of this study was to monitor the Indian national rowing team`s training regime and the changes that occur in the rowers` body composition, muscle cell damage, and training load markers during the phases of preparation for an international competition.